La Rse Dans Les Pme Camerounaises: Etude Exploratoire A Partir Des Schemes cognitifs des proprietaires-dirigeants (Global Journal of Management and Business Research, 2018)
This study is interested in the owner-manager of the SME and particularly in the analysis of his cognitive schemes concerning CSR. Using cognitive mapping as a technique for representing and analysing cognitive patterns, the results of this study reveal that human resources, consumers and to a lesser extent the community are the stakeholders whose wellbeing is of concern to SME's owners manager. However, their motivations for implementing CSR are not the same. For some, CSR is a lever for achieving strategic objectives, while for others it is an objective in itself, and not a means for achieving other ends.
Keywords: SMEs; CSR; owner-managers; cognitive schemes